IMPLEMENTASI KETELADANAN PELAYANAN TUHAN YESUS KRISTUS BERDASARKAN YOHANES13:1-20 BAGI GURU PENDIDIKAN AGAMA KRISTEN DI KECAMATAN ANJONGAN KABUPATEN MEMPAWAH PROVINSI KALIMANTAN BARAT - Wahyuni, Sri; Uriptiningsih, Ana Lestari; Hermina, Hermina (RERUM: Journal of Biblical Practice, 2025)
This study entitled Implementation of the Exemplary Service of the Lord Jesus Christ Based on John 13: 1-20 for Christian Religious Education Teachers in Anjongan District, Mempawah Regency, West Kalimantan Province. Aims to teach about the formation of students. Teachers do not only teach Christian Religious Education, but more about formation. because of the development of science and technology or changes in the era. Especially based on the curriculum of 1975, 1983, and 1993-1994. The hope is to achieve a perfect balance between the physical, mental, spiritual, and daily social life of students and teachers. by emphasizing the moral and ethical principles held by Christians. This study involved 75 Christian religious teachers in Anjongan District, Mempawah Regency, West Kalimantan. The research used quantitative with a descriptive method determined by the Likert scale method. The results of the study are in accordance with the first hypothesis proposed. Thus, the proposed hypothesis is declared accepted. It is known that the results of the calculation using the Confidence Interval statistic at a significance level of 5% produced Lower Bound and Upper Bound 174.5900 - 180.4827 which is in the medium interval, the second hypothesis test using linear regression analysis states that the Serving with love dimension (D1) has the highest determination value of 0.956 with a contribution to the endogenous variable of 90.4%, the third hypothesis test analysis According to Classification and regression trees (CRT), age is the most dominant background category. This forms the application of the example of Jesus Christ in serving based on John 13: 1-20 for Christian Teachers in Elementary Schools throughout Anjongan District, Mempawah Regency, West Kalimantan (Y). The age background is able to improve by 13.279 points. Penelitian ini yang berjudul Implementasi Keteladanan Pelayanan Tuhan Yesus Kristus Berdasarkan Yohanes13:1-20 Bagi Guru Pendidikan Agama  Kristen Di Kecamatan Anjongan Kabupaten Mempawah Provinsi Kalimantan Barat. Bertujuan untuk mengajarkan tentang pembentukan peserta didik. Guru tidak hanya mengajarkan Pendidikan Agama Kristen, namu lebih ke pembentukan. karena kemjaun ilmu pengetahuan dan teknologi atau trasnpormasi zaman. Khususnya berdasarkan kurikulum tahun 1975, 1983, dan 1993-1994. Harapannya adalah untuk mencapai keseimbangan yang sempurna antara keberadaan fisik, mental, kerohanian, dan kehidupan sosial sehari-hari siswa dan guru. dengan menekankan prinsip-prinsip moral dan etika yang dipegang oleh umat Kristen. Studi ini melibatkan 75 guru agama kristen di Kecamatan Anjongan Kabupaten Mempawah, Kalimantan Barat. Peneliatan mengunakan kuantitatf dengan metode deskriptif yang ditentukan metode skala likert. Hasil Penelitian sesuai dengan hipotesis pertama  yang diajukan. Dengan demikian hipotesis yang diajukan dinyatakan diterima. Diketahui hasil perhitungan dengan mengunakan statistik Confidence Interval pada taraf signifikansi 5% dihasilkan Lower Bound dan Upper Bound 174,5900 – 180,4827 yang berada pada interval sedang, pengujian Hipotesis kedua pengujian menggunakan analisis Regresi linear menyatakan dimensi Melayani dengan kasih (D1) memiliki nilai determinasi tertinggi yaitu 0,956 dengan kontribusi terhadap endogenous variabel sebesar 90,4%, pengujian Hipotesis ketiga  analisis Menurut Classification dan regression trees (CRT), usia adalah kategori latar belakang yang paling dominan. Ini membentuk penerapan contoh Yesus Kristus dalam melayani berdasarkan Yohanes 13:1-20 Bagi Kalangan Guru Kristen Di Sekolah Dasar Se-Kecamatan Anjongan Kabupaten Mempawah Kalimantan Barat (Y). Latar belakang usia mampu memperbaiki sebesar 13,279 point.